Mental health in South African adolescents living with HIV: correlates of internalising and externalising symptoms - Boyes, Mark; Cluver, L.; Meinck, F.; Casale, M.; Newnham, E. (Routledge, 2018)
Although declining in all other age groups, AIDS-related deaths among adolescents are increasing. In the context of HIV, mental health problems are associated with negative health outcomes, including non-adherence to life-saving ART. For effective programming it is essential to identify factors associated with psychological outcomes in this population. Adopting a socioecological perspective, we aimed to identify correlates of internalising and externalising symptoms in a large, representative sample of South African adolescents living with HIV. HIV-positive adolescents (n = 1060), who received care in public health facilities in South Africa’s Eastern Cape, completed measures of internalising and externalising symptoms. Hypothesised correlates included HIV and health-related factors (physical health, mode of infection, medication side-effects, disclosure, stigma), health-service related factors (negative interactions with clinic staff, clinic support group), interpersonal factors (abuse, bullying victimisation, social support), parenting-related factors (orphanhood, positive parenting, parental monitoring, parent communication), as well as individual and demographic-related factors (self-efficacy, age, gender, urban/rural location, poverty). Correlates operating across a variety of contexts were identified. Bullying victimisation, self-efficacy, and positive parenting may be particularly salient intervention targets as they were associated with better outcomes on most or all mental health measures, can be addressed without directly targeting adolescents living with HIV (reducing the chances of accidental exposure and stigma), and are associated with better adolescent mental health in South Africa more generally.